SHARIA COMPLIANCE MODEL OF THE ISTISHNA CONTRACT IN SHARIA HOUSING DEVELOPMENT: A CONCEPTUAL REVIEW OF ISLAMIC ECONOMIC LAW - Dahlia Firdausi (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2026)
The istishna contract is widely used in the development of Sharia housing in Indonesia. However, its implementation may create Sharia compliance problems when it is not supported by an adequate understanding of fiqh muamalah principles and positive legal regulations. This article aims to formulate a conceptual sharia compliance model for istishna contracts as an effort to strengthen consumer protection in sharia housing development. This study uses normative legal research with conceptual and statutory approaches. The legal materials include DSN-MUI fatwas, relevant laws and regulations, and literature on Islamic economic law. The results show that sharia compliance in istishna contracts must be established through fulfillment of the pillars and requirements of the contract, clarity of object specifications, transparency of price and delivery time, proportional risk allocation, and systematic sharia supervision. The proposed model is arranged into four stages, namely pre-contract, contract formation, implementation, and post-handover. The model is expected to serve as a normative basis for developing fair, transparent, and sharia-compliant istishna practices in sharia housing.